The Political Economy of Contemporary Insecurity in Nigeria: Theoretical Issues and Explanations - Sarafa, Ogundiya Ilufoye; Monday, Titus Utibe (International Journal of Criminology and Sociology, 2024)
This paper examined the nature of contemporary insecurity in Nigeria. The paper adopts a qualitative methodology, and the data were gathered using documentary sources. It anchors on political economy approach using game theoretic modeling as theoretical framework. The paper argued that Nigerian state is currently facing internal security threats from separatist demands and ethnic militias to terrorism, cattle rustling, kidnapping for ransom, armed banditry, and armed robbery among others. It further stressed that Nigeria's frighteningly high level of insecurity makes its citizens live in constant fear. That Nigeria's socio-economic development has been badly impacted by this insecurity, which also has an influence on the credibility of Nigeria's international image. In order to address Nigeria's worries about insecurity, this paper concluded with policy recommendations, primarily for the National Assembly that corrupt practices must be addressed in order to restore peace in Nigeria. Also, to facilitate effective governance, which is necessary for upholding peace and stability in the country, the National Assembly must use the power of the legislative power derived from the constitution to improve responsiveness, transparency and accountability.